AN ASYMPTOTIC FORMULA FOR THE SUM OF THE NEGATIVE EIGENVALUES OF SECOND ORDER DIFFERENTIAL OPERATOR GIVEN IN INFINITE INTERVAL - Baksi, Ozlem; Ismayilov, Sedi (YILDIZ TECHNICAL UNIV, 2005)
Asymptotic formul is founded for the sum of negative eigenvalues of the operator L in L-2[0,infinity) space, where L formed by l(y) = (p(x) y'(x))' - q(x)y(x) differantial expression and y(0) = 0 bounded
Keywords: Self-adjoint operator; Negative eigen value; Spectrum; Asymptotic; Engineering